EDUKASI BOOKLET HIV/AIDS UNTUK PENINGKATAN PENGETAHUAN REMAJA - Vitrilina Hutabarat; Stefani Anastasia Sitepu; Mutiara Dwi Yanti; Nurul Aini Siagian; Husna Sari (INSTITUT KESEHATAN DELI HUSADA, 2021)
HIV/AIDS is a problem that is still difficult to solve and is often referred to as the iceberg problem, only a few appear on the surface but many have been infected without knowing the symptoms. HIV or Human Immunodeficiency Virus is a type of virus that attacks / infects white blood cells causing a decrease in human immunity. HIV cases have increased from year to year. years of being infected with HIV. This Community Service aims to carry out online education booklets so that there is an increase in knowledge of adolescents related to HIV. This Community Service was carried out using zoom media in 1 (one) day involving high school teenagers, the Deli Husada Midwife Student Association (IMABIDDA) and working with the IT team